The Linnean foundations of zoological and botanical nomenclature - Kraus, Otto (Zootaxa, 2008)
In contrast to primary taxonomic research, nomenclature is a tool to be used in information retrieval and with the aim of ensuring world-wide understanding. Radical changes to its guiding principles would be counterproductive as they would produce disorder in a system of internationally accepted conventions that have developed and matured over decades. Classifications are ordering systems. They are even more utilitarian in function and should not be constantly adapted to potentially ephemeral phylogenies. In principle, the Linnaean foundations of nomenclature and classification survive. Attempts to introduce fundamental changes or even alternatives were proposed a century too late to get enforced; they therefore failed.